Hubungan Serapan P dengan Pertumbuhan Setek Lada pada Aplikasi Kompos Ampas Tahu dan Jerami Padi - Danie Indra Yama; Okto Ivansyah; Ricka Astriy (Agrotechnology Research Journal, 2021)
This research aims to determine the effect of tofu dregs compost and rice straw compost to growth of pepper cuttings. The research by experiment to determine the best dosage of tofu dregs compost and rice straw compost and to determine the relationship between P uptake and pepper cuttings growth. The experiment design was a factorial Randomized Complete Block Design consisting of two factors (dosage of dregs of tofu and rice straw compost) with 4 levels respectively, each of combination replicated 3 times. The dosage dregs of tofu compost are without dregs of tofu, 200, 250, and 300 g per plant). Dose of rice straw compost are without rice straw compost,75, 100, and 125 g per plant. The results showed that the combination tofu dregs compost and rice straw compost did not effect on all growth parameters. Application dregs of tofu compost of 300 g per plant and 75 g per plant of rice straw compost had an effect on the formation of roots and leaves. The relationship between growth and P uptake was not significant.